Fracture investigation in starch-based foods - Skamniotis, CG; Patel, Y; Charalambides, MN; Elliott, M (Royal Society, 2016)
The study of oral processing and specifically cutting of the food piece during mastication can lead towards optimization of products for humans or animals. Food materials are complex biocomposites with a highly nonlinear constitutive response. Their fracture properties have not been largely investigated, while the need for models capable of predicting food breakdown increases. In this study, the blade cutting and the essential work of fracture (EWF) methodologies assessed the fracture behaviour of starch-based pet food. Tensile tests revealed rate-dependent stiffness and stress softening effects, attributed to viscoplasticity and micro-cracking, respectively. Cutting data were collected for 5, 10 and 30 mm s(−1) sample feed rates, whereas the EWF tests were conducted at 1.7, 3.3 and 8.3 mm s(−1) crosshead speeds corresponding to average crack speeds of 4, 7 and 15 mm s(−1), respectively. A reasonable agreement was achieved between cutting and EWF, reporting 1.26, 1.78, 1.76 kJ m(−2) and 1.52, 1.37, 1.45 kJ m(−2) values, respectively, for the corresponding crack speeds. These toughness data were used in a novel numerical model simulating the ‘first’ bite mastication process. A viscoplastic material model is adopted for the food piece, combined with a damage law that enabled predicting fracture patterns in the product.